Right Temporoparietal Junction Modulates In-Group Bias in Facial Emotional Mimicry: A tDCS Study - Peng, Shenli; Kuang, BeiBei; Hu, Ping (Frontiers in Behavioral Neuroscience, 2020)
The present study employs transcranial direct current stimulation (tDCS), a non-invasive brain stimulation technique, to explore the possible role of the right temporoparietal junction (rTPJ) in regulating in-group bias in facial emotional mimicry. Participants received either anodal or cathodal stimulation, or they were assigned to a sham condition. After that, they passively viewed a series of video clips depicting different emotions (happiness and anger) that were performed either by ethnic in-group or out-group models. The emotion-specific muscle activities, zygomatic major (ZM) and corrugator supercilii (CS), were recorded simultaneously as the index of facial emotional mimicry. The results firstly confirm the in-group bias in facial emotional mimicry in the sham condition, as shown in prior studies, though it only occurs in happy mimicry. Moreover, the in-group bias in facial emotional mimicry is modulated by the cortical excitability over the rTPJ, which may be attributed to the accompanied change of overlap of the mental representations of in-group and out-group. This study provides a close look at the neural underpinning of the modulation of facial emotional mimicry by group membership, and highlights the role of rTPJ in on-line control of co-activated self and other representation in social cognition.